Design and Experimental Study of Spoon-Clamping Type Garlic Precision Seeding Device. (4th June 2022) - Zhang, Xinyan; Yi, Shujuan; Tao, Guixiang; Zhang, Dongming; Chong, Jun
Abstract : In order to realize the mechanized sowing operation of garlic and ensure that the position of garlic scales is planted upright-position, a spoon-clamping type garlic precision seeding device is designed. The device is composed of seed box, seeder, righting fittings, and so on. This paper adopts the method of theoretical analysis; combined with the characteristics of garlic, the key components of the sowing device have been optimized and designed; and the final form of the device is determined. The one-factor experiment and multifactor experimental studies were carried out, and the optimal working parameter combination of the device was obtained by using the response surface methodology and mathematical modeling method, and finally, the optimized working parameter combination was verified. The results showed that the spoon-clamping type garlic sowing device could meet the operational requirements of garlic mechanized sowing. This study has certain theoretical and practical significance for the mechanization development of garlic.